2018
DOI: 10.4103/1319-2442.225199
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Induced nephropathy: Pathophysiology, risk factors, and prevention

Abstract: Contrast-induced acute kidney injury is a common iatrogenic complication associated with increased health resource utilization and adverse outcomes, including short- and long-term mortality and accelerated progression of preexisting renal insufficiency. The incidence of contrast-induced nephropathy (CIN) has been reported to range from 0% to 24%. This wide range reported by the studies is due to differences in definition, background risk factors, type and dose of contrast medium used, and the frequency of othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(42 citation statements)
references
References 2 publications
1
40
0
1
Order By: Relevance
“…Patients undergoing a contrast procedure, especially those with risk factors such as chronic kidney disease, accompanying with hypotension, contrast medium volume, congestive heart failure, aging, diabetes mellitus, and cardiovascular disease would be risky to develop mild to serious complications. [21,22] In this meta-analysis, it was found that the administration of periprocedural allopurinol could cause reduction in the incidence of CI-AKI in patients undergoing interventional procedures (RR 0.39, 95% confidence interval[CI] 0.20,0.74, P = .004; Fig. 3) which leading to a significantly lower level of Scr and BUN (SMD -0.50, 95% CI −0.79,−0.21, P = .0009; SMD −0.40, 95% CI −0.60,−0.20, P < .0001; respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Patients undergoing a contrast procedure, especially those with risk factors such as chronic kidney disease, accompanying with hypotension, contrast medium volume, congestive heart failure, aging, diabetes mellitus, and cardiovascular disease would be risky to develop mild to serious complications. [21,22] In this meta-analysis, it was found that the administration of periprocedural allopurinol could cause reduction in the incidence of CI-AKI in patients undergoing interventional procedures (RR 0.39, 95% confidence interval[CI] 0.20,0.74, P = .004; Fig. 3) which leading to a significantly lower level of Scr and BUN (SMD -0.50, 95% CI −0.79,−0.21, P = .0009; SMD −0.40, 95% CI −0.60,−0.20, P < .0001; respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The post-CT oral hydration can easily be done at home and monitored by the patient's family. Third, previous studies [28][29][30] investigated CIN by estimated glomerular filtration rate (eGFR), whereas the current study could not test the eGFR pre-and post-CT. Thus, further studies of outpatients and high-risk groups in Gaza Strip-Palestine are necessary.…”
Section: Discussionmentioning
confidence: 79%
“…Patient characteristics, including old age, hypotension, diabetes mellitus, pre-existing renal impairment, history of renal transplantation, anemia and use of nephrotoxic drugs are known to significantly increase the risk of post-procedural AKI. Similarly, procedural factors, including contrast media properties, contrast media volume and number of procedures within 72 h also influence the probability of AKI ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of AKI following the use of contrast media has been reported to be 0-24% ( 2 ). Although in most cases, AKI is transient, irreversible renal injury may occur in a proportion of patients, leading to progressive kidney damage, which may require prolonged hospitalization and result in long-term adverse effects ( 4 ).…”
Section: Introductionmentioning
confidence: 99%